2017
DOI: 10.1097/pts.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient Safety Culture in Community Pharmacies

Abstract: Understanding the safety culture of community pharmacies can help identify areas of strength and those that require improvement. Improvement efforts that focus on staffing, work pressure, and pace in community pharmacies may lead to better safety culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 29 publications
6
43
1
Order By: Relevance
“…The level of safety culture in current survey was lower than the Western studies (Aboneh, Stone, Lester, & Chui, 2020;Sharp et al, 2019) and similar to previously published Iranian papers (Arab, Moghri, Akbari Sari, & Rahimi Forooshani, 2013;Azami-Aghdash et al, 2015…”
Section: Discussionsupporting
confidence: 89%
“…The level of safety culture in current survey was lower than the Western studies (Aboneh, Stone, Lester, & Chui, 2020;Sharp et al, 2019) and similar to previously published Iranian papers (Arab, Moghri, Akbari Sari, & Rahimi Forooshani, 2013;Azami-Aghdash et al, 2015…”
Section: Discussionsupporting
confidence: 89%
“…The result was similar to a study conducted in Wisconsin which reported overall rating was very high (Good 21%, Very good 44% and Excellent 26%) [24].…”
Section: Plos Onesupporting
confidence: 88%
“…Statements related to physical space and environment (83.1%) received the second highest PRR among the 11 patient safety culture composites finding. This percentage was slightly lower than a study reported in Kuwait (88.2%) [6] but higher than study done in Wisconsin (73%) [24].…”
Section: Plos Onecontrasting
confidence: 72%
See 1 more Smart Citation
“…21,22 Therefore, in October 2012, the US AHRQ developed and piloted the Community Pharmacy Survey on Patient Safety Culture, a survey instrument filled by pharmacy personnel to assess patient safety culture in community pharmacies. [23][24][25][26] The AHRQ pilot study reported that the main strengths observed in the patient safety culture within US community pharmacies were in the areas of patient counselling and communication openness, while the main weakness was related to staffing, work pressure and pace. Studies from other countries have assessed the patient safety culture within community pharmacy settings using the AHRQ survey.…”
Section: Introductionmentioning
confidence: 99%